Smart Materials, Adaptive Structures and Intelligent Systems, Volume 2 2008
DOI: 10.1115/smasis2008-605
|View full text |Cite
|
Sign up to set email alerts
|

Energy Harvesting by Pyroelectric Effect Using PZT

Abstract: This paper considers energy harvesting using pyroelectric materials such as PZT-5A and thin-films. A simple model is used to predict the power generated based on the measured temperature of the material as a function of time. The measured and predicted results are presented and compared. In particular, the measured peak power density for a PZT-5A sample was 0.23 μWcm−2 for a maximum temperature rate of approximately 15 °Cs−1. The predicted peak power density under the same boundary conditions for thin-film lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Pyroelectric current can be used not only for temperature measurement sensors but also for waste energy harvesting. Any source of waste energy with temperature changes over time is suitable to produce pyroelectricity and can be harvested for many applications [12,[14][15][16][17]…”
Section: Introductionmentioning
confidence: 99%
“…Pyroelectric current can be used not only for temperature measurement sensors but also for waste energy harvesting. Any source of waste energy with temperature changes over time is suitable to produce pyroelectricity and can be harvested for many applications [12,[14][15][16][17]…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the harvested energy could be compatible with that used in autonomous sensors working in low-duty-cycle switched-supply mode [13][14][15][16][17]. Here, non-linear pyroelectric using the hysteresis dependence on temperature was investigated [13,14].…”
Section: Introductionmentioning
confidence: 84%
“…As we have discussed in the previous section, although some of the lead-free materials have exhibited superior thermal energy harvesting performance to that of the lead-based pyroelectric materials, the lead-based materials show superior FoMs for applications such as infrared sensors, which make them an excellent choice for commercial sensor application. In the quest for excellent materials for PyEH application, a plethora of studies have been reported on PZT- and PMN-PT-based ceramics and their thin films [64,85,108,114,115,116,117,118,119,120,121]. The phase transformations of the ceramics play a huge role in the PyEH energy density and efficiency.…”
Section: Pyroelectricity In Ferroelectric Materialsmentioning
confidence: 99%